Synthesis and characterization of fused‐thiophene containing naphthalene diimide n‐type copolymers for organic thin film transistor and all‐polymer solar cell applications. Issue 19 (28th June 2013) - Yuan, Mingjian; Durban, Matthew M.; Kazarinoff, Peter D.; Zeigler, David F.; Rice, Andrew H.; Segawa, Yukari; Luscombe, Christine K.
ABSTRACT Naphthalene diimide copolymers are attractive n‐type materials due to their high electron affinities, high electron mobilities, and exceptional stability. Herein, we report a series of NDI‐fused‐thiophene based copolymers with each copolymer differing in the number of fused thiophenes in the donor monomer. Increasing the number of fused‐thiophene moieties within an NDI‐copolymer backbone is shown to not only enable tuning of the electronic structure but also improve charge mobilities within the active layer of organic field‐effect transistors. Electron mobilities and on/off ratios as high as 0.012 cm2 V−1 s‐1 and Ion/Ioff > 105 were measured from n‐channel thin‐film transistors fabricated using NDI‐xfTh copolymers. Bulk heterojunction solar cell devices were also fabricated from the NDI‐xfTh copolymer series in blends with poly(3‐hexylthiophene) (P3HT) with PNDI‐4fTh‐based devices yielding the largest Jsc (0.57 mA cm−2) and fill factor (55%) in addition to the highest measured PCE for this series (0.13%). © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4061–4069